A study on the association of rs7950273 polymorphism in the PDGFD with ischaemic stroke in the Chinese Han population. (2nd January 2016) - Han, Jingjun; Li, Huanlian; Wu, Deqiang; Zeng, Nafen; Wu, Zhihua; Cai, Longgan; Chen, Weiqiang; Zuo, Wei; Zhang, Yanwei
Abstract: Background : The association between the platelet-derived growth factor D (PDGFD) gene and atherosclerosis has been widely proven, whereas the relationship between the PDGFD gene and ischaemic stroke remains unconfirmed. Aim : A case-control study was performed to further evaluate the association of the C → G mutation of rs7950273 in the PDGFD gene with ischaemic stroke (IS) in a Chinese Han population. Subjects and methods : This study recruited 3033 cases and 2807 controls from general hospitals in the southern, central and northern areas of China. The MGB probe and Taqman 7900HT Sequence Detection System were applied for genotyping. Results : Genotype was not significantly associated with ischaemic stroke in total. After adjustment for gender, age, BMI, hypertension, diabetes mellitus and smoking, the CG and GG genotypes were still not associated with ischaemic stroke ( p  = 0.892 and p  = 0.582 for CG and GG, respectively). Conclusion : This study suggests that the polymorphism of rs7950273 in the PDGFD gene is not associated with ischaemic stroke in the Chinese Han population. Further studies on the gene–gene and gene–environment interactions for the PDGFD gene and ischaemic stroke are needed.